PIROLA, Ricardo Figueiredo. Senzala insurgente - Brito, Ênio José da Costa (REVER: Revista de Estudos da Religião, 2014)
Resenha: PIROLA, Ricardo Figueiredo. Senzala insurgente. Malungos, parentes e rebeldes nas fazendas de Campinas (1832). Campinas. Editora UNICAMP, 2011. ISBN 978-85-268-09934-5. 303 p.